Transmission Control Protocol and Active Queue Management together against congestion: cross-comparison through simulations. (October 2019) - Grazia, Carlo Augusto; Patriciello, Natale; Klapez, Martin; Casoni, Maurizio
Most Internet traffic is carried by the Transmission Control Protocol (TCP) nowadays, even in the case of real-time services. Detecting and mitigating the congestion is one of the primary tasks of this protocol, in fact, different TCP versions are defined by their congestion control algorithms. Furthermore, Active Queue Management (AQM) algorithms share the same goal of congestion mitigation with TCP; in particular, the most efficient congestion control occurs when AQM and TCP work together. This paper presents a brief survey and a cross-comparison of the latest and most important TCP and AQM variants, then provides an evaluation of a different kind of performance on the ns-3 network simulator over various types of environments (multiple Round Trip Time, long delay, different congestion levels, etc.). In any shared bottleneck, the choice of the TCP-AQM couple to adopt is crucial. We will show that the results are not univocal and the "one size fits all" solution does not exist. Moreover, the proper couple depends on the performance that we want to boost and on the environment that we have to deal with.